2009
DOI: 10.1186/ar2825
|View full text |Cite
|
Sign up to set email alerts
|

Why are women predisposed to autoimmune rheumatic diseases?

Abstract: The majority of autoimmune diseases predominate in females. In searching for an explanation for this female excess, most attention has focused on hormonal changes - both exogenous changes (for example, oral contraceptive pill) and fluctuations in endogenous hormone levels particularly related to menstruation and pregnancy history. Other reasons include genetic differences, both direct (influence of genes on sex chromosomes) and indirect (such as microchimerism), as well as gender differences in lifestyle facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
134
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(153 citation statements)
references
References 78 publications
12
134
0
7
Order By: Relevance
“…Our study showed that women with SCD were 10 times more likely to have RA than men with SCD which is significantly greater than the reported gender differences in the general population where women were 3 times more likely to develop RA compared to men [15]. SCD could potentially have an increased risk of developing CTD similar to that speculated for patients with beta-thalassemia trait and its association with higher rates of RA [1,16].…”
Section: Prevalence Of Positive Serology and Connective Tissue Diseasesupporting
confidence: 47%
“…Our study showed that women with SCD were 10 times more likely to have RA than men with SCD which is significantly greater than the reported gender differences in the general population where women were 3 times more likely to develop RA compared to men [15]. SCD could potentially have an increased risk of developing CTD similar to that speculated for patients with beta-thalassemia trait and its association with higher rates of RA [1,16].…”
Section: Prevalence Of Positive Serology and Connective Tissue Diseasesupporting
confidence: 47%
“…However, hormonal--sexual complications (such as menstrual disorders and early menopause) were not evaluated in the present study. Perhaps the relationship between early adverse effects and the patients' sex is associated with the higher prevalence of certain diseases among women, or with more severe disease than among men, rather than being directly related to the use of CP [27]. This issue surely requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] The reason for the female predominance in autoimmune diseases is not completely understood; nevertheless, the finding of a similar pattern of female dominance in ANA production suggests that hormonal or other factors in females play a role in this process. 18,19 Several authors reported prevalence of ANA in RA has been variable in several published series ranging from 10% to 70%. 20 The variability in prevalence is probably due to multiple factors including patient selection and technical factors such as type of substrate used in the test, characteristics of the fluorescent reagents, etc.…”
Section: Discussionmentioning
confidence: 99%